Optical mibrobottle resonator for formaldehyde (CH2O) liquid sensing / Al Noman Abdullah - Abdullah, Al Noman (2018)
In recent years, microbottle resonator (MBR) has attracted an excessive attention on account of its various applications such as sensors, lasing and filters. Compared to the other optical microresonators (OMRs) it has some advantages of fast tunability through the strain application, better control over the coupling by optical tapered microfiber and in the spectrum the probability of attaining a great number of equally-spaced modes. The MBR was fabricated with an SMF-28 silica optical fiber by “soften-and-compress” method which created a bulge area on the fiber to become formed as bottle shape. The formaldehyde (CH2O) liquid which was used for this work has 37% purity of formalin with other ions. In this investigation, the influence of whispering gallery mode (WGM) on an optical microbottle resonator (OMBR) and its consequence on liquid (formaldehyde, CH2O) sensing is demonstrated. The MBR then excited using a tapered optical microfiber of 5 μm waist diameter and for each concentration levels of liquid the Q-factor (quality factor) noted as >105. Comparison between the MBR and the bare fiber has stated based on four specific parameters such as linearity, sensitivity, p-value and standard deviation where MBR has shown better potentiality than the bare fiber towards liquid sensing for the sensor. Moreover, the outcome of MBR was explained with two different diameters of tapered microfiber which are 8 μm and 10 μm. The MBR energized through both tapered fiber and also stated their effect for the liquid sensing in this work. For both experiments, the MBR was categorized by three significant constraints such as bottle distance